South-South cooperation: the role of development banks and the Agenda 2030 - Álvarez Herrera, Ana María (Revista Española de Desarrollo y Cooperación, 2023)
The BAPA+40 presents an opportunity to grow and diversify the South-South cooperation (SSC) framework, including the actors involved and their contribution to the 2030 Agenda for Sustainable Development. Given the potential of national, regional and international development banks, it is appropriate to explore and support meaningful projects that further develop SSC.